2015
DOI: 10.1016/j.smallrumres.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of milk production losses in Valle del Belice sheep following experimental infection of Mycoplasma agalactiae

Abstract: a b s t r a c tEconomic losses due to contagious agalactia (CA) in small ruminant herds are mainly associated with significant reductions in or complete loss of dairy production, mortality, abortions, ill thrift, early culling and costs of control. With the aim of estimating milk production losses caused by CA, 46 primiparous lactating Valle del Belice ewes were monitored after experimental infection. Sixty days after lambing, two ewes were each experimentally infected with a single dose of 10 8 CFU/ml of a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…With regard to the effect of losses in milk production, the estimated losses were approximately 12.5% and ranged from 1514 g for healthy ewes to 1327 g for infected ewes. The lower milk production of infected sheep was similar to results reported by Todaro et al (2015) who found a decrease of about 17% of milk in experimentally infected ewes of the same sheep breed. Our results showed that infection with M. agalactiae had a significant impact on milk production.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…With regard to the effect of losses in milk production, the estimated losses were approximately 12.5% and ranged from 1514 g for healthy ewes to 1327 g for infected ewes. The lower milk production of infected sheep was similar to results reported by Todaro et al (2015) who found a decrease of about 17% of milk in experimentally infected ewes of the same sheep breed. Our results showed that infection with M. agalactiae had a significant impact on milk production.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were obtained by Contreras et al (2008) in goat bulk-tank milk. An increase in somatic cell count was also reported in ewes experimentally infected with M. agalactiae (Bergonier et al 1996;Todaro et al 2015). In a study of bulk tank milk from different goat herds co-infected with various Mycoplasma spp., the presence of different Mycoplasma spp.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is generally thought that milk proteins increase during mastitis due to increases in blood albumins and immunoglobulins influx as an immune response [ 3 , 18 ]. Protein percentage increases have been reported during M. agalactiae experimental mastitis in small ruminant [ 60 ].…”
Section: Discussionmentioning
confidence: 99%